Metal measurement of fossil galaxy groups: XMM-Newton data analysis of NGC 6482 - Gülmez, Emine (My University, 2023)
Galaxy groups are structures that comprising more than half of all galaxies. They have hot (10^7 K) intra-group medium (IGrM) that emit X-rays and exhibit numerous emission lines of elements synthesized by stars and during supernovae. Galaxy groups have lower gravitational potentials compared to rich galaxy clusters and the difficulty of detecting them optically. Therefore X-ray observations which carries significant signatures about metal content provide an ideal means for studying galaxy groups. In this study, we aimed to identify elements dispersed into the environment by supernovae by examining the hot plasma surrounding the member galaxies of the nearest known fossil galaxy group, NGC6482 (z~0.012), using observations (~142 ks) from the European Photon Imaging Camera (EPIC) of the XMM-Newton satellite sent into its operational orbit by the European Space Agency (ESA). We measured the abundance of Fe, Mg, Si, and S elements in the NGC 6482's IGrM. We discussed the implications of the element ratios and amounts in relation to the Fe element.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2023
Keywords: Fosil grup; NGC6482; Metal bolluk; Kimyasal zenginleşme; Galaksi grupları; XMM-Newton